Muscle wasting: an overview of recent developments in basic research. Issue 3 (28th August 2014) - Palus, Sandra; von Haehling, Stephan; Springer, Jochen
Abstract : The syndrome of cachexia, i.e., involuntary weight loss in patients with underlying diseases, sarcopenia, i.e., loss of muscle mass due to aging, and general muscle atrophy from disuse and/or prolonged bed rest have received more attention over the last decades. All lead to a higher morbidity and mortality in patients, and therefore, they represent a major socio‐economic burden for the society today. This mini‐review looks at recent developments in basic research that are relevant to the loss of skeletal muscle. It aims to cover the most significant publication of last 3 years on the causes and effects of muscle wasting, new targets for therapy development, and potential biomarkers for assessing skeletal muscle mass. The targets include the following: (1) E‐3 ligases TRIM32, SOCS1, and SOCS3 by involving the elongin BC ubiquitin‐ligase, Cbl‐b, culling 7, Fbxo40, MG53 (TRIM72), and the mitochondrial Mul1; (2) the kinase MST1; and (3) the G‐protein Gαi2 . D(3)‐creatine has the potential to be used as a novel biomarker that allows to monitor actual change in skeletal muscle mass over time. In conclusion, significant development efforts are being made by academic groups as well as numerous pharmaceutical companies to identify new target and biomarker muscles, as muscle wasting represents a great medical need, but no therapies have been approved in the last decades.